KRUGER, James Thomas [Jimmy] Inventory of documents - KRUGER, James Thomas [Jimmy] (ARCA, 2018)
Private papers of J.T. Kruger, National Party MP Prinshof [1966-1979], Senator Nominated [1979-1980], President of the Senate [1979-1980], Deputy Minister of Police [1972-1974], Interior [ 1972-1974], Social Welfare and Pensions [1972-1974], Justice [1974], Prisons [1974], Minister of Prisons [1974-1979], Justice [1974-1979], Police[1974-1979].
COVERAGE 1951-1979; 74 Files; 1,20 Metres. AUDIO CASSETTES IN ARCA COLLECTION = 15
Keywords: KRUGER, James Thomas [Jimmy]; Inventories; Politicians; National Party